Meninjau Kembali Pemikiran Edward Said tentang Studi Orientalisme dalam Pandangan Poskolonial - Samudra Eka Cipta; Pendi Kurniawan (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
The main content of Edward Said's concept of Orientalism, its development and history as a branch of science, and how the field of Orientalism studies is used as a tool of domination, colonialism, and imperialism in the postcolonial perspective. Edward Said himself is a Palestinian-American academic, literary critic, and political activist. The writing in the article is a literature review of Edward Said's work.